Expression levels of the tetratricopeptide repeat protein gene ttc39b covary with carotenoid-based skin colour in cichlid fish - Ahi, Ehsan Pashay (Biol Lett, 2020)
Carotenoid pigments play a major role in animal body colouration, generating strong interest in the genes involved in the metabolic processes that lead from their dietary uptake to their storage in the integument. Here, we used RNA sequencing (RNA-Seq) to test for differentially expressed genes in a taxonomically replicated design using three pairs of related cichlid fish taxa from the genera Tropheus and Aulonocara. Within each pair, taxa differed in terms of red and yellow body colouration, and high‐performance liquid chromatography (HPLC) analyses of skin extracts revealed different carotenoid profiles and concentrations across the studied taxa. Five genes were differentially expressed in all three yellow–red skin contrasts (dhrsx, nlrc3, tcaf2, urah and ttc39b), but only the tetratricopeptide repeat protein-coding gene ttc39b, whose gene product is linked to mammalian lipid metabolism, was consistently expressed more highly in the red skin samples. The RNA-Seq results were confirmed by quantitative PCR. We propose ttc39b as a compelling candidate gene for variation in animal carotenoid colouration. Since differential expression of ttc39b was correlated with the presence/absence of yellow carotenoids in a previous study, we suggest that ttc39b is more likely associated with the concentration of total carotenoids than with the metabolic formation of red carotenoids.